THE EFFECTIVENESS COMBINATION OF HYPNOBREASTFEEDING AND BREAST EXERCISES ON BREAST MILK PRODUCTION TIME IN THIRD TRIMESTER PREGNANT WOMEN - Reni, Dian Puspita; Puspitaningsih, Rezki; Wati, Ratna; Nurachma, Evy (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background : Global Breastfeeding Scorecard report that evaluates breastfeeding data from 194 countries, the percentage of infants under six months who are exclusively breastfed is only 9.79% (9 countries). Meanwhile, in Indonesia exclusive breastfeeding for 0-6 months is only 50.67%. Several factor inhibiting exclusive breastfeeding such as lack of breast care during antenatal and physiological conditions of the breast before or during breastfeeding. Pregnant women have difficulty expressing breast milk on the first day until third day after giving birth. One of the alternative method to speed up the breast milk production time is using hypnobreastfeeding and breast exercises.Methods: Quasi Experiment with Static Group Comparison design. Hypnobreastfeeding and breast exercises are independent variables. Breast milk production time is the dependent variable. The research sample was third trimester pregnant women whose breast milk has not come out at the Clinic Samarinda City. Total sample are 38 respondents and used purposive sampling. Samples were selected by according to inclusion and exclusion criteria. Technique analysis data bivariate used Chi-Square.Result: ρvalue (0.016) < α (0.05). The relative risk (RR) is 5,152.Conclusion: The combination of hypnobreastfeeding and breast exercises is effective on breast milk production time in third trimester pregnant women at the Clinic Samarinda City. Researchers suggest that health workers can provide training on hypnobreastfeeding and breast exercises to pregnant women whose breast milk has not come out (from 28-36 weeks of gestation), training can be done from 36 weeks of gestation.